Facilitation by Tree Species in Variable Retention Harvesting for the Restoration of Monoculture Plantations in Southern China. (January 2019) - Jiang, Jun; Lu, Yuanchang; Wang, Ling; Liu, Xianzhao; Cai, Daoxiong; Jia, Hongyan; Ming, Angang; Chen, Beibei
Facilitation can drive the successional dynamics and change the restoration trajectory of degraded forests. However, the relative importance of facilitation by tree species after variable retention harvesting is unclear. We used a field experiment to evaluate the effect of two facilitator species, Castanopsis fissa (C. fissa) and Manglietia glauca (M. glauca), managed with variable retention harvesting, on the development of two target species, Castanopsis hystrix (C. hystrix) and Erythrophloeum fordii (E. fordii), in a Masson pine ( Pinus massoniana ) monoculture. The following variables were measured for all of the four interplanted tree species: structural growth, regeneration, aboveground biomass accumulation, leaf area index, and soil conditions. The results indicate that the abundance, growth, and aboveground biomass were relatively greater in plots planted with C. fissa compared with M. glauca and that the target species performed best with 50% retention harvesting of C. fissa, with an improved establishment of both target species indicating a positive interaction. In addition, the regeneration, leaf area index and soil conditions differed between the two facilitators in the variable retention harvesting treatments because of the different intrinsic characteristic of the facilitators. In summary, our results imply that managers have considerable flexibility to employ various types of facilitation schemes coupled with different harvesting systems for successful short-term restoration within a monoculture.